Business strategy development model for applying knowledge management in construction - Abu Adi, Wedad; Hiyassat, Mohammed; Lepkova, Natalija (Journal of Civil Engineering and Management, 2021)
This study aims at developing a knowledge management (KM) model that construction companies can apply for effective knowledge management implementations in their businesses. In developing the proposed model, a mixed methodology of analysing related literature and identifying the gaps in some existing models intended for the construction industry is applied. In addition, a questionnaire and interviews approaches are conducted to prepare, enhance, strengthen and validate the developed model. The major finding of this study is proposing a new KM model – named as BAN model – that fits potential conditions for construction contracting firms, especially enterprises that are small in size and nonadopting KM. The developed model comprises six main stages: (1) preliminary stage; (2) development of an organizational strategy stage; (3) start-up stage; (4) implementation stage; (5) monitoring and evaluation stage; and (6) derivation of short- and long-term KM values. The proposed model is capable of filling and solving the gaps in existing knowledge management models and defining major success factors in KM implementation. The benefits of the proposed model include the enhancement of the KM implementation process, facilitation of the decision-making process, attainment and maintenance of competitive advantages, improvement of innovation, and continuance of effective KM performance.